Students' Perception on Project-Based Learning in Teaching Speaking at Vocational High School - Johanes Climacus Setyo Karjono; Sabrina Sintyasakti, Nimas; Vitalya Gemilang, Adria (Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this study lies in its potential to revolutionize the way speaking skill is developed in vocational high schools. By exploring the students’ perception of Project-Based Learning, teachers can gain new perspectives on how to engage students in meaningful and practical speaking activities. This approach not only helps students prove their speaking skills but also prepares them for real-world situations where effective communication is crucial for success. This study used a descriptive qualitative approach. The qualitative data in this study come from a variety of sources, including an observation checklist, field notes, and interviews. The data were collected using semi structured- interview. The data were gathered from 72 students. In classroom activities, Project-Based Learning frequently necessitates access to technology, materials, and resources that may not easily available in vocational high school. To be able ensure fair access to high-quality education for schools, this issue must be resolved.